1998
DOI: 10.1172/jci1699
|View full text |Cite
|
Sign up to set email alerts
|

Direct evidence for the importance of endothelium-derived nitric oxide in vascular remodeling.

Abstract: The vascular endothelium mediates the ability of blood vessels to alter their architecture in response to hemodynamic changes; however, the specific endothelial-derived factors that are responsible for vascular remodeling are poorly understood. Here we show that endothelial-derived nitric oxide (NO) is a major endothelial-derived mediator controlling vascular remodeling. In response to external carotid artery ligation, mice with targeted disruption of the endothelial nitric oxide synthase gene (eNOS) did not r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

34
513
7
13

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 756 publications
(567 citation statements)
references
References 38 publications
34
513
7
13
Order By: Relevance
“…Our findings are also in concordance with the observations in eNOS knockout mice, which have been found to have increased IMT. 41 In the present study, polymorphism in intron 4 of eNOS gene was not associated with carotid IMT. Conversely, Japanese investigators in haemodialysed patients found the odds ratio for carotid plaque was increased to 3.72 by the 4a allele of the intron 4 polymorphism.…”
Section: Discussionsupporting
confidence: 39%
“…Our findings are also in concordance with the observations in eNOS knockout mice, which have been found to have increased IMT. 41 In the present study, polymorphism in intron 4 of eNOS gene was not associated with carotid IMT. Conversely, Japanese investigators in haemodialysed patients found the odds ratio for carotid plaque was increased to 3.72 by the 4a allele of the intron 4 polymorphism.…”
Section: Discussionsupporting
confidence: 39%
“…6 A dysfunctional endothelium loses not only the capacity to regulate vascular tone, but also its anti-thrombotic and anti-aggregation properties for leukocytes and platelets. 7 Thromboxane A2, produced by the platelets, is the most important agent producing vasoconstriction, is increased in diabetics, and the smooth muscle of the vessels has a higher susceptibility to it.…”
Section: Pathogenesis Of Arterial Hypertension In Diabetesmentioning
confidence: 99%
“…[1][2][3][4][5] Indeed, reduction of endothelial NO synthesis (endothelial dysfunction) predisposes the blood vessel to arteriosclerosis, [1][2][3][4][5] and the eNOS-deficient (eNOS-KO) mice exhibit accelerated vascular lesion formation. 6,7 As pharmacological tools to inhibit endothelial NO synthesis, synthetic L-arginine analogues have been used in vitro and in vivo. Among them, N -nitro-L-arginine methyl ester (L-NAME) is the most frequently used agent.…”
mentioning
confidence: 99%